Transparansi Pengelolaan Keuangan Daerah Pemerintah Kabupaten/Kota di Kalimantan Barat - Endang Kusmana; Bob Mustafa; Uray Muhammad Noor (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This study aims to describe the level of transparency in regional financial management that has been carried out by the Regency/City Government based on the Minister of Home Affairs Instruction No. 188.52/1797/SJ of 2012. This research was conducted in 14 districts/cities in West Kalimantan. The data analysis method used in this research is the descriptive quantitative analysis which focuses on measuring the transparency index of regional financial management. Descriptive statistics in this study were used to look at the level of regional transparency in general and based on each indicator at the APBD planning stage, APBD implementation stage, and APBD reporting and accountability stages consisting of 10 (ten) indicators. The results of the study show that the average level of transparency in regional management for 14 district/city governments in West Kalimantan is still very low, namely 5.30% or overall the district/city governments in West Kalimantan are still in the qualification of insufficient transparency. . The Sanggau District Government has the highest regional financial management transparency index, with a score of 4.5 out of a maximum score of 29 (15.52%). Meanwhile, Mempawah Regency Government, Ketapang Regency Government, Bengkayang Regency Government, Sekadau Regency Government, Melawi Regency Government, Kayong Utara Regency Government, Kubu Raya Regency Government, and Pontianak City received the lowest score, and index, namely a score of 1 (3.45%).Keywords: Transparency, Regional Finance